Factors influencing behaviour intention of job seekers towards social media recruitment in Malaysia - Chan, Siew Min (2018)
This study was aimed to investigate the behaviour intention to use of job seekers towards social media in Malaysia. To specifically examine the in-depth of intention to use of job seekers, background and issues related to the research topic has been discussed. This study is designed to achieve the following objectives: To investigate the significant relationship between the independent variables and dependent variables. The independent variables are (1) usefulness of social media, (2) information quality, (3) website usability, (4) privacy/ security concern. While the dependent variables are behaviour intention of job seekers towards social media recruitment sites. This research might also be beneficial to certain parties‟ recruiting companies, government, future researchers and other jobseekers or employers. Furthermore, reviews of literature by previous author and researcher are provided in order to further explain the association between the variables and the explanation of behaviour intention to use social media recruitment. In this research, data are collected from primary sources where questionnaires are distributed to 200 respondents in Malaysia using convenient sampling technique, in which the respondent who experienced in using social media to find or get a job before. Statistical Package for the Social Sciences (SPSS) software version 21.0 is used to carry out the research to construct new findings in the association between the independents variables and dependents variables. The results and findings are then demonstrated in few different parts which included descriptive analysis for demographic profile, constructs for central tendencies measurement, measurement of scale and the inferential analysis. Lastly, all the findings in the research are concluded in the last chapter. Implications of the study are also further described, as well as the limitations and delimitation of the study. Not to mention, several recommendations for future research are provided to sums up the entire completed research.